2002
DOI: 10.1029/2001jd000609
|View full text |Cite
|
Sign up to set email alerts
|

Surface water dynamics in the Amazon Basin: Application of satellite radar altimetry

Abstract: [1] Satellite radar altimetry has the ability to monitor variations in surface water height (stage) for large wetlands, rivers, and associated floodplains. A clear advantage is the provision of data where traditional gauges are absent. As part of an international program, a complete altimetric analysis of the Amazon Basin is being undertaken. Here, an updated and more rigorous evaluation of the TOPEX/POSEIDON (T/P) data set is presented for the first $7.5 years of the mission. With an initial study group of 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
228
0
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(240 citation statements)
references
References 31 publications
8
228
0
4
Order By: Relevance
“…It represents a unique source of data for floodplain, as the in-situ data records are generally located on the river mainstream. Although the radar altimetric measurements are still suffering severe limitations (Birkett, 1998;Birkett et al, 2002), the capability to sample, from one cycle to another, both mainstream and floodplain is a clear advantage compared with traditional in-situ measurements. This aspect is essential because it has been shown that the water volume stored in floodplains cannot be inferred from the flood extent, nor the elevation of the flood by its extent.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It represents a unique source of data for floodplain, as the in-situ data records are generally located on the river mainstream. Although the radar altimetric measurements are still suffering severe limitations (Birkett, 1998;Birkett et al, 2002), the capability to sample, from one cycle to another, both mainstream and floodplain is a clear advantage compared with traditional in-situ measurements. This aspect is essential because it has been shown that the water volume stored in floodplains cannot be inferred from the flood extent, nor the elevation of the flood by its extent.…”
Section: Resultsmentioning
confidence: 99%
“…1 : We explained and clarified the notions of water storage variation and water volume calculated from half peak flow integrated discharge in the additional paragraph 3.5. 2 : Many studies such as Birkett et al (2002) or Oliveira Campos et al (2003 showed the quality of water level derived from radar altimetry measurements. We added in figure 4 a comparison of the in-situ water levels at Manaus gauge station and the altimeter derived water level obtained 8.5 km upstream.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in remote sensing have demonstrated that some hydraulic variables can be measured reliably from satellites. For example, satellite altimetry (Topex/Poseidon (T/P), Jason-1, ERS, and Envisat missions) has been used for systematic monitoring of water levels of large rivers, lakes, and floodplains, now providing an ∼15 year long time series [Birkett, 1998;Birkett et al, 2002;Gennero et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…Observations of river inundation areas, water levels, and flow variability from orbital sen sors have the potential to directly measure the runoff component of the Earth's hydrologic cycle [Birkett et al, 2002;Brakenridge et al, 1998;Sippel et al, 1994Sippel et al, ,1998Townsend, 2001 ]. A remote-sensing-based measurement strategy for rivers and streams is emerging: Surface water data can be collected, their accuracy evaluated, and the results disseminated with out regard to political boundaries.The results can be used to address a wide variety of ap plications.…”
Section: Pages 185188mentioning
confidence: 99%